Research on Copyright Issues of Artificial Intelligence-Generated Works - Xue, Shudan (Transactions on Economics, Business and Management Research, 2026)
With the advancement of artificial intelligence technology, artificial intelligence-generated works have been widely integrated into all aspects of social life. How to protect their copyright is an inevitable issue in contemporary legal practice. On the premise of meeting the requirements of originality, intellectual achievement attribute and tangible reproduction, artificial intelligence-generated works can constitute works in the sense of copyright law and have the rationality of being protected by copyright law. Taking the principle of closest connection and the principle of encouraging creation as the core, the copyright should be mainly attributed to the user. At the same time, a multi-dimensional mechanism including contract agreement, technical measures and liability sharing should be adopted to balance the interests among developers, investors and users, exert the maximum institutional efficiency, and enable it to continue to shoulder the mission of encouraging creation and prospering culture. Artificial intelligence-generated works; Copyright law; Work attribute; Right attribution.